Design and implementation of a Context-Aware Health Service Platform (CAHS) - Siham Belhadi; Rachid Merzougui (Institute of Advanced Engineering and Science, 2019)
Computers are no match to humans in deducing situational information from their environment and in using it in their interactions. The advent of the context-aware applications seems to offer a way out to the computer that is not context-sensitive. The context aware applications can adapt their behaviors according to the perceived context or situation, without explicit user intervention, thereby providing human-centric services. To simplify the complexity of developing applications, context aware framework, which introduces context awareness into the environment where the applications are executed, is highlighted to provide a homogeneous interface involving generic context management and adaptation solutions. This papier has focused on the design of Context-Aware Health Services (CAHS) platform, which provide a health applications framework embedded on mobile devices. Our proposed platform is capabilities for context manager and adaptations according to context changes. It is designed to base on the SOA principles for achieving a flexible and dynamic architecture.